Under the Blow of the Counterrevolution - Makhno, Nestor Ivanovich, 1889-1934; Archibald, Malcolm, 1943- (Edmonton : Black Cat Press, 2009)
Nestor Makhno (1888-1934) was a peasant anarcho-communist who organized an experiment in anarchist values and practice in southeast Ukraine during the Russian Revolutions of 1917 and the subsequent Civil War (1917-1921). Under the blows of the counterrevolution is the second volume of his memoirs which describes his odyssey through revolutionary Russia in the spring of 1918. Driven from his Ukrainian village by a German invasion, he wanders through a nation torn by civil war, encounters various remarkable personalities, and survives hair-raising adventures